Ectopic teeth in a patient with Gorham-Stout disease previously treated by biphosphonates: a case report - Le Donne Mélanie; Jaby Philippe; Farge Pierre; Gleizal Arnaud (EDP Sciences, 2020)
Introduction: Gorham-Stout disease is a rare idiopathic condition of the bone that is characterized by a massive and spontaneous osteolysis, with a vascular or lymphatic proliferation in bone, which is then replaced by fibrous tissue. Observation: a 16-year-old patient was referred to the maxillofacial surgery department to remove ectopic teeth bilaterally in the ramus. He had Gorham-Stout disease, managed for many years in orthopedic surgery department for a lower limb lesion and in neurosurgery department for a breach of the meninges. He was treated for 4 years with bisphosphonates. The removal of the ectopic teeth went well, with a simple postoperative course. Discussion: Gorham-Stout disease physiopathology remains unknown. Facial bones are often involved, especially the mandible. There are many possible treatments, but, due to the rarity of the disease, no therapeutic consensus exists. Bisphosphonates seem to be a good way to control this condition. So far, no case of bisphosphonates related osteonecrosis of the jaw has been reported in children. Conclusion: Gorham-Stout disease can involve the mandible and may lead to ectopic teeth.